If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3v-42=5(v-6)
We move all terms to the left:
3v-42-(5(v-6))=0
We calculate terms in parentheses: -(5(v-6)), so:We get rid of parentheses
5(v-6)
We multiply parentheses
5v-30
Back to the equation:
-(5v-30)
3v-5v+30-42=0
We add all the numbers together, and all the variables
-2v-12=0
We move all terms containing v to the left, all other terms to the right
-2v=12
v=12/-2
v=-6
| 2n-13=-19(16+4n) | | a/9=1/23 | | 289=69-u | | 2(x-2)=5x-16 | | -30=12-6x | | 5/8=3/y | | 6x+12+7x=-4 | | -2(x^2-7)^2+3=-47 | | 4(k+9)=4(k+9) | | −4−0.2x+11=−0.8x+10 | | 5x−7=58 | | −4−0.2x+11=−0.8x+10 | | 5x−2=3x+1 | | 12=0.005x | | 116(x−40)=5+x | | 11-3a+6=27 | | 5(x−2)=3x+1 | | 6(x+6)=6x+4 | | −5(3x−15)=2(x−1)−59 | | 10h+4=11 | | 7b^2+3b+42=0 | | 3x-6+4x=18-x | | 3(x-8)=7x-20 | | -x/5=22 | | 1/d+6=10 | | 6+x+9=6+x+9 | | 9x=7(×+1.75) | | 5(2y-3)=(2y+3) | | 2z=8z+2 | | 3u+16=u | | x5-7=-5 | | 16x9x=14 |